Perspektif suku Dawan tentang kampanye komunikasi bencana menggunakan Natoni - Andung, Petrus Ana; Messakh, Jokobis Johanis; Doko, Meryana Micselen (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
The utilization of various local wisdoms in disaster mitigation efforts has been widely implemented, including in South Central Timor Regency. However, the effectiveness of these methods in delivering disaster communication messages—specifically in terms of practicality, reliability, and message strength—has not been thoroughly examined. This study aims to explore the perceptions of the people of West Timor, particularly those living in disaster-prone areas, regarding the effectiveness of Natoni as a medium for disaster communication campaigns. This study employs a qualitative research design, specifically a case study method. Data collection techniques include in-depth interviews and participant observation. Data analysis was conducted using the Miles and Huberman interactive analysis model. The findings show that the Dawan community has a positive perspective on the use of Natoni as a folk medium for disaster communication campaigns. Natoni can be utilized as a platform to embed disaster education messages within its performances. The Dawan people of West Timor view Natoni as an effective folk medium for conveying disaster education messages. Natoni is considered powerful in delivering messages due to its integral role in sacred traditional rituals, making the messages more trusted and adhered to by the community. Academically, this study emphasizes the importance of researching traditional media as an effective tool for disseminating development information, particularly in rural areas with limited technological access. Practically, the study reinforces previous research that local wisdom-based folk media possesses the reliability to convey development messages in rural communities.